Sturge-Weber syndrome: A case report - De, Dipankar; Periyakaruppan, Muthiah; Prakash, Sandeep Chandra; Sunilbala, K; Singh, Kh Ibochouba; Singh, L Ranbir (Indian Journal of Child Health, 2015)
Sturge-Weber syndrome (SWS) is a rare disorder that occurs sporadically with a frequency of 1:50,000. It is a neurocutaneous syndrome, characterized by a facial capillary malformation (port-wine stain), abnormal blood vessels on the brain (leptomeningeal angioma), and the eyes leading to glaucoma. The patient may present with seizure, hemiparesis, stroke-like episodes, headache, and developmental delay. Here, we report a case of SWS in a 5-month-old baby presenting with the features of port-wine stain, focal seizure, and intracranial calcification.